PEMBERITAAN TRAGEDI KANJURUHAN DALAM TAYANGAN YOUTUBE NARASI MATA NAJWA: ANALISIS WACANA KRITIS VAN DIJK : Bahasa Indonesia - Fasilatul Nur Ellya; Yarno Yarno; Idhoofiyatul Fatin (STKIP Siliwangi, 2023)
The commotion after Arema FC's match against Persebaya at Malang's Kanjuruhan Stadium caused many victims. This has attracted the attention of various parties. In this regard, this study aims to analyze the structure of the text, social cognition, and social context in Mata Najwa's episode of the Kanjuruhan tragedy. This research includes a qualitative descriptive study using Youtube videos as a data source. Data collection techniques used are documentation, observe, and record. Data analysis techniques include data reduction, data presentation, and conclusions. The research results found in Mata Najwa's Kanjuruhan tragedy episode through Teun van Dijk's critical discourse analysis, namely in the text dimension found micro-structural elements indicating the main problem, namely the chronology of the Kanjuruhan tragedy incident. The analysis of social cognition produces the most dominant scheme, namely the event scheme. There are two discourses that are emphasized in social cognition, namely the justification related to tear gas and the chaos that occurred due to fans taking to the field. This research has implications in the social context that can help identify injustices contained in the language and discourse used by groups in power.